Minimum stomatal conductance: implications for describing the genetic control of transpiration - Reuning, Gretchen, author; Bauerle, William, advisor; McKay, John, committee member; Qian, Yaling, committee member (Colorado State University. Libraries, 2013)
Minimum stomatal conductance (g0) makes a significant contribution to the rate of water loss in plants. The influence of g0 on water use efficiency (WUE) has implications for plant drought tolerance and adaptation, thus we propose that g0 can be used as a trait to describe the genetic control of water use in leaf transpiration models. In the model species, Arabidopsis thaliana, g0 exhibits both environmental and genetic variation. We explored one g0 quantitative trait locus (QTL) by measuring and simulating transpiration for two A. thaliana accessions Kas-1 and Tsu-1, as well as recombinant inbred lines (RILs) from a reciprocal cross of the two parental lines. Using a three-dimensional spatially explicit plant process model, MAESTRA, we aimed to: (1) test the accuracy of transpiration prediction for Kas-1 and Tsu-1 using measured g0 values, (2) parameterize MAESTRA with Tsu-1, Kas-1, and RIL g0 values to predict transpiration of RILs containing either Tsu-1 and Kas-1 alleles at the g0 QTL, and (3) determine if a relationship exists between g0 values under well-watered and drought conditions in A. thaliana. MAESTRA accurately predicted A. thaliana transpiration for Kas-1 and Tsu-1 accessions when parameterized with measured g0 values. There was no significant difference between measured and simulated transpiration estimates for both accessions, with Tsu-1 simulated transpiration 5.2% lower than the mean measured, and Kas-1 simulated transpiration 1.4% higher than measured. On average, Kas-1 transpired 73% as much water as Tsu-1. Due to the lack of specific knowledge of RIL physiology aside from g0, simulating RIL transpiration with varying g0 values yielded non-significant results. However, based on the simulated means for RIL transpiration using RIL, Kas-1, and Tsu-1 g0 values, we show that g0 parameterization predicts daily transpiration when all other parameters are held constant at Tsu-1 or Kas-1 measured and presumed physiology. This further points to the importance of g0 for transpiration predictions. Data on additional g0 QTL could aid in predicting transpiration from novel genotypes such as RILs containing multiple combinations of alleles from parental genotypes. We found that accessions with relatively high well-watered g0 values showed sharper declines in g0 during drought compared to accessions with lower g0 values under well-watered conditions (p < 0.0001). The use of plant physiological models for predicting transpiration of novel genetic lines will benefit from the further knowledge of the genetic control of g0.